Correlation between subjective well-being and quality of life in elderly - Nataša Egeljić-Mihailović; Duška Jović; Darija Knežević; Jelena Pavlović (Биомедицинска истраживања, 2020)
Introduction: The aim of the study was to examine the correlation between subjective well-being and quality of life of the elderly in relation to their demographic characteristics, health, social and financial status. Methods: The study sample was comprised of 159 subjects of both sexes and of older age. The respondents underwent research in Banja Luka in the premises of the Association of Pensioners of the Republic of Srpska, senior citizens' clubs when coming to some of financial institutions to get help, to open bank accounts etc., as well as in the premises where pensioners gather to socialize and communicate. The survey questionnaire developed for the purpose of the paper and adapted to this population was used in the study. The survey questionnaire consisted of the following elements: sociodemographic data, self-assessment concerning the quality of life and Quality of Life Scale for the Elderly. Results: The study included a total of 159 subjects, 56.6% males and 43.4% females, of whom the majority were 65-75 years old (67.3%). The average health status (M = 2.17; SD = 0.68) was higher than the expected value, while the social status (M = 1.93; SD = 0.60) and the social needs (M = 1.91; SD = 0.72) were slightly lower compared to theoretical mean. Furthermore, the financial status had an average value (M = 2.08; SD = 0.59). The distribution of social needs was unsatisfactory. The obtained value of the Self-Perceived Quality of Life Scale was within the range of the theoretical mean values (M = 5.54, SD = 2.47), indicating that the distribution of the obtained quality of life values was symmetrical. Conclusion: Financial status significantly affects the quality of life of the elderly. The distribution of social needs is unsatisfactory. The level of education significantly affects the quality of life: highly educated respondents have a better health, social and financial status compared to the elderly with a lower level of education.
Keywords: quality of life; elderly; assessment; financial status; social needs